(untitled) (Journal of the College of Education for Women, 2019)
It is out of question that USA foreign policy has a great superiority andinfluence all over the world.This study deals with all dimensions; aims; and challenges of the Americanforeign policy. It aims to answer the following question: within the current changes inthe world, how can the aims of the American foreign policy be realized?